The Comparison of Color Stability of Aloe Vera Gel and Chlorhexidine Solution on Acrylic Teeth - Farhang Mahboub; Amin Nourizadeh; Armin Izadpanah (International Journal of Dentistry)
Background. There is insufficient knowledge about aloe vera color change property on acrylic teeth compared to other denture cleaners, especially chlorhexidine solution (CHX). Objective. The present study aimed to compare the color change property of the aloe vera and chlorhexidine solution on denture acrylic teeth. Methods. This study was experimental in vitro study design conducted in the dental laboratory of Tabriz University of Medical Sciences, Iran, 2021. The sample size in each group was 21 acrylic teeth which were randomly divided into aloe vera gel 100% and chlorhexidine solution 2% groups. Tooth colors were measured by a spectrophotometer (Spectro Shade Micro, MHT S.P.A., Milan, Italy). The immersion time in both groups was 36 hours. Data analyzed using an independent t-test was used at a 95% of confidence level. Results. The comparison of the total color differences (ΔE) between the two groups was not statistically significant after 36 hours of immersion (P=0.440). In the chlorhexidine group, the brightness of teeth was lower than that in the aloe vera group (P=0.002). Conclusions. Clinicians should be aware that aloe vera gel does not change the color of denture acrylic teeth after 36 hours of immersion similar to the chlorhexidine solution. For patients who cannot use chlorhexidine, aloe vera gel is a good cleaner for denture acrylic teeth without worrying about the color change of the denture. It can be considered an acceptable cleaner for denture acrylic teeth.